A model for electrochemical insertion limited by a phase transition process - eilpt - Adhoum N.; Bouteillon J.; Dumas D.; Poignet J.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper deals with electrochemical insertion into a cathodic material. New results on modeling of the influence of a solid phase transformation on the shape of voltamograms are presented. The original experiments concern the insertion of sodium into carbon during the cathodic reduction of molten NaF at 1020 °C, but in the present manuscript emphasis on the theoretical aspects of the work is put. Phase transformations during electrochemical insertion are taken into account, with various values for parameters such as the thermodynamic biphase equilibrium potential, the compared diffusion and phase transformation kinetics, and the electrode thickness. The voltamograms calculated present very specific features; some of them have already been observed experimentally in literature.